Identification of distinctive interferon gene signatures in different types of myositis. (17th September 2019) - Pinal-Fernandez, Iago; Casal-Dominguez, Maria; Derfoul, Assia; Pak, Katherine; Plotz, Paul; Miller, Frederick W.; Milisenda, Jose C.; Grau-Junyent, Josep M.; Selva-O'Callaghan, Albert; Paik, Julie; Albayda, Jemima; Christopher-Stine, Lisa; et al.
Abstract : Objective: Activation of the type 1 interferon (IFN1) pathway is a prominent feature of dermatomyositis (DM) muscle and may play a role in the pathogenesis of this disease. However, the relevance of the IFN1 pathway in patients with other types of myositis such as the antisynthetase syndrome (AS), immune-mediated necrotizing myopathy (IMNM), and inclusion body myositis (IBM) is largely unknown. Moreover, the activation of the type 2 interferon (IFN2) pathway has not been comprehensively explored in myositis. In this cross-sectional study, our objective was to determine whether IFN1 and IFN2 pathways are differentially activated in different types of myositis by performing RNA sequencing on muscle biopsy samples from 119 patients with DM, IMNM, AS, or IBM and on 20 normal muscle biopsies. Methods: The expression of IFN1- and IFN2-inducible genes was compared between the different groups. Results: The expression of IFN1-inducible genes was high in DM, moderate in AS, and low in IMNM and IBM. In contrast, the expression of IFN2-inducible genes was high in DM, IBM, and AS but low in IMNM. The expression of IFN-inducible genes correlated with the expression of genes associated with inflammation and muscle regeneration. Of note, ISG15 expression levels alone performed as well as composite scores relying on multiple genes to monitor activation of the IFN1 pathway in myositis muscle biopsies. Conclusions: IFN1 and IFN2 pathways are differentially activated in different forms of myositis. This observation may have therapeutic implications because immunosuppressive medications may preferentially target each of these pathways.